Research on Evolutionary Knowledge and Attitudes in the Czech Republic and the New Standardized Instrument (EEQ) for Research in this Field of Study - Dvořáková, Radka Marta (Scientia in educatione, 2022)
Evolution is the key concept in modern biology. Understanding basic evolutionary principles is, therefore, key to quality biological education. This text firstly aims to summarize the issues in the field of research of evolutionary knowledge and attitudes in the Czech Republic in the European context and, secondly, to introduce a new research tool for this research field. Research on evolutionary knowledge and/or attitudes towards evolution has been and is still being studied by several European researchers and research teams. However, the results of studies published so far do not provide much room for further comparison. The main problems are the different types of respondents and the fact that the authors use very diverse research instruments whose validity or reliability has seldom been firmly established. A group of researchers associated with the project COST 17127 tried to overcome the problems mentioned above. They developed a standardized research instrument EEQ (=Evolution Education Questionnaire). Its advantage is its wide range of applicability (types of respondents, time range of the questionnaire or evolutionary topic; in addition, the questionnaire is suitable for research on evolutionary knowledge as well as attitudes) and the existence of 23 language mutations, including Czech, which predestines it for use throughout Europe.